(untitled) (GIST – Education and Learning Research Journal, 2016)
Through a mixed methods approach, this study collected data on the current state of IEP teachers’ perceived self-efficacy in teaching ESL readig, and the factors that may affect this. Statistical analyses of surveys show a number of relationships among the factors explored: years of teaching, perceived self-efficacy, amount of pre-service training, amount of professional development and availability of resources. To detail the experiences of these instructors, responses of follow-up interviews are discussed. Taken together, the results of this study underscore the need for ESL teacher trainign programs and IEP institutes to devote greater effort in prepraring faculty to teach ESL reading skills effectively.